The role of assertive behavior in conflict resolution and negotiation among Generation Z librarians - Fitri, Laili Sofia; Masruri, Anis (Faculty of Communication, Padjadjaran University, 2026)
Background: Librarians are required to be assertive amid changing times and the dynamics of Generation Z, which is beginning to dominate the workplace. Assertive behavior is a communication skill that can be learned to reduce conflict. Studies on the application of assertive behavior among Generation Z librarians are still limited; therefore, research is needed to fill this gap. Purpose: This study aims to identify the assertive behavior of Generation Z librarians in conflict resolution and negotiation within library settings, using Janette S. Caputo’s theory. The main research question is: How do Generation Z librarians apply various forms of assertive statements in the context of library service interactions?Methods: This study utilizes a descriptive qualitative approach. Informants were determined using purposive sampling based on several criteria, and nine informants were obtained from school libraries (SMPN 29 Bandar Lampung, SMKN Padang Cermin, SD Kreativa, SMK Muhammadiyah 3 Metro), universities (Universitas Bhayangkara Jakarta Raya, Institut Sains Teknologi Nasional, and Politeknik Kesuma Bangsa), and public libraries (Kabupaten Pringsewu and Kabupaten Pesisir Barat). Data collection was carried out through structured interviews.Results: The study reveals that Generation Z librarians exhibit various forms of assertive behavior. They demonstrate Simple Assertion by facilitating effective information retrieval. Empathetic Assertion is shown through adjustments in communication styles. Soft Assertion appears in the form of support, positive feedback, and appreciation toward coworkers. Anger Assertion is expressed professionally. Confrontation Assertion is reflected in polite renegotiation of work agreements. Negative Assertion involves acknowledging mistakes and maintaining healthy communication. Assertive Disengagement is demonstrated by postponing discussions assertively when conditions are unsuitable.Conclusions: Generation Z librarians apply various forms of assertive behavior in conflict resolution and negotiation in libraries.